2015
DOI: 10.1007/s00134-015-4095-4
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged glucocorticoid treatment is associated with improved ARDS outcomes: analysis of individual patients’ data from four randomized trials and trial-level meta-analysis of the updated literature

Abstract: Prolonged methylprednisolone treatment accelerates the resolution of ARDS, improving a broad spectrum of interrelated clinical outcomes and decreasing hospital mortality and healthcare utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
242
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(270 citation statements)
references
References 40 publications
10
242
0
7
Order By: Relevance
“…These data favoured steroid treatment, with a high degree of evidence for the duration of initial assisted breathing and ventilator-free day outcomes, in particular. In the trial-level meta-analysis, glucocorticoid treatment was associated with an increase in mechanical ventilation-free and ICU-free days and with a reduced risk of in-hospital mortality (total mortality risk ratio 0.52, 95% CI 0.33-0.82) [48]. Risk of nosocomial infection did not increase with glucocorticoid treatment.…”
Section: Treatmentmentioning
confidence: 91%
See 2 more Smart Citations
“…These data favoured steroid treatment, with a high degree of evidence for the duration of initial assisted breathing and ventilator-free day outcomes, in particular. In the trial-level meta-analysis, glucocorticoid treatment was associated with an increase in mechanical ventilation-free and ICU-free days and with a reduced risk of in-hospital mortality (total mortality risk ratio 0.52, 95% CI 0.33-0.82) [48]. Risk of nosocomial infection did not increase with glucocorticoid treatment.…”
Section: Treatmentmentioning
confidence: 91%
“…No clear differences between early versus late treatment initiation was noted, whereas patients undergoing a rapid tapering of the study drug after the patient achieved unassisted breathing showed a greater risk of returning to mechanical ventilation. Secondary outcomes included mechanical ventilation-free days, ICU-free days, hospital mortality, time to death by hospital discharge or by day 28 and infectious complications [48]. These data favoured steroid treatment, with a high degree of evidence for the duration of initial assisted breathing and ventilator-free day outcomes, in particular.…”
Section: Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…In this context, the current analysis by Meduri et al [5] is welcome. These authors conducted a two-part analysis-(1) individual patient data meta-analysis (IPDMA) from trials with methylprednisolone and (2) an updated trial-level metaanalysis including additional randomised controlled trials (RCTs) with hydrocortisone in early ARDS-and have reported that steroids accelerated the resolution of ARDS, leading to reduced ventilatory assistance, hospital mortality and health care utilisation [5]. However, these conclusions appear to contradict those of the ARDS Network LaSRS study [4], which contributed 56 % of the patients to the IPDMA.…”
mentioning
confidence: 86%
“…A recent analysis of individual patient data from four randomized trials combined with a trial-level meta-analysis of the updated literature demonstrated that early and prolonged GC treatment accelerated resolution of ARDS, decreased hospital mortality and healthcare utilization without increasing the risk of infection [11]. The suggested mechanism underlying these beneficial effects is that prolonged treatment with low-dose GC may overcome ARDS-associated deficient GC-GRa activity [12].…”
mentioning
confidence: 99%